The Omega-3 Index Response to an 8 Week Randomized Intervention Containing Three Fatty Fish Meals Per Week Is Influenced by Adiposity in Overweight to Obese Women - Richardson, Christine E.; Krishnan, Sridevi; Gray, Ira J.; Keim, Nancy L.; Newman, John W. (Frontiers in Nutrition, 2022)
Background: The Dietary Guidelines for Americans (DGA) recommends consuming ~225g/wk of a variety of seafood providing >1.75g/wk of long-chain omega-3 fatty acids to reduce cardiovascular disease risk, however individual responses to treatment vary. Objective: This study had three main objectives. First, to determine if a DGA-conforming diet (DGAD), in comparison to a typical American diet (TAD), can increase the omega-3 index (OM3I), i.e. the red blood cell mol% of eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA). Second, to identify factors explaining variability in the OM3I response to dietary treatment. Third to identify factors associated with the baseline OM3I. Design: This is a secondary analysis of a randomized, double-blind 8wk dietary intervention of overweight/obese women fed an 8d rotating TAD (n =20) or DGAD (n =22) registered at www.clinicaltrials.gov as NCT02298725. The DGAD-group consumed 240g/wk of Atlantic farmed salmon and albacore tuna in three meals with an estimated EPA + DHA of 3.7 ± 0.6 g/wk. The TAD-group consumed ~160g/wk of farmed white shrimp and a seafood salad containing imitation crab in three meal with an estimated EPA + DHA of 0.45 ± 0.05 g/wk. Habitual diet was determined at baseline, and body composition was determined at 0 and 8wks. Red blood cell fatty acids were measured at 0, 2 and 8wk. Results: At 8wk, the TAD-group OM3I was unchanged (5.90 ± 1.35% to 5.80 ± 0.76%), while the DGAD-group OM3I increased (5.63 ± 1.27% to 7.33 ± 1.36%; p <0.001). In the DGAD-group 9 of 22 participants achieved an OM3I >8%. Together, body composition and the baseline OM3I explained 83% of the response to treatment variability. Baseline OM3I (5.8 ± 1.3%; n =42) was negatively correlated to the android fat mass (p =0.0007) and positively correlated to the FFQ estimated habitual (EPA+DHA) when expressed as a ratio to total dietary fat (p =0.006). Conclusions: An 8wk TAD did not change the OM3I of ~6%, while a DGAD with 240g/wk of salmon and albacore tuna increased the OM3I. Body fat distribution and basal omega-3 status are primary factors influencing the OM3I response to dietary intake in overweight/obese women.